Embodied strategies for public speaking anxiety: evaluation of the Corp-Oral program - García-Monge, Alfonso; Guijarro-Romero, Santiago; Santamaría-Vázquez, Eduardo; Martínez-Álvarez, Lucio; Bores-Calle, Nicolás (Frontiers in Human Neuroscience, 2023)
Background: Public speaking is an indispensable skill that can profoundly influence success in both professional and personal spheres. Regrettably, managing anxiety during a speech poses a significant challenge for many of the population. This research assessed the impacts of a Corp-Oral program, designed to manage public speaking anxiety in university students, based on, body awareness, embodied message techniques, simulation, embodied visualization, body transformation, and gesture enhancement. Methods: Thirty-six students (61% women; Mage=20.22, SD=1.23 years) were randomly assigned to either an experimental group (n=18), which underwent the Corp-Oral program, or a control group (n=18). Self-perceived anxiety, heart rate, and electroencephalography were measured in a pre-test and a post-test. Results: The study reveals that the Corp-Oral program significantly (p<0.005) reduced both physiological responses (heart rate) and self-reported measures of anxiety. The alteration was more noticeable in self-reported anxiety measures (a decrease of 33.217%) than in heart rate (a decrease of 4.659%). During the speech, the experimental group exhibited increased cortical activation in areas related to emotional regulation, consciousness, sensorimotor integration, and movement control. A significant increase in frontal alpha asymmetry was observed for the experimental group in the post-test, but there were no significant variations in the theta/beta ratio. Conclusion: These findings underline the benefit of managing public speaking anxiety not merely by reducing it but by channeling it through embodied strategies. These strategies could lead to greater action awareness that would cushion the physiological effect of the anxiety response and help generate a better self-perception of the anxiety state.